Wastewater influent and effluent concentrations from on-site package plants in Northern Sweden and Finland ... : Avloppsvattens inkommande och utgående koncentrationer från minireningsverk i norra Sverige och Finland ... - Vidal, Brenda (Luleå University of Technology, 2023)
The data contains influent and effluent concentrations of traditional parameters measured in on-site package plants for domestic wastewater treatment serving single houses or small communities (2-30 person equivalent). The parameters analysed include organic matter, suspended solids, nutrients (phosphorus and nitrogen compounds) and indicator bacteria, as well as other physicochemical parameters such as temperature, pH and turbidity, and chloride as a tracer compound to detect dilution effects. Additional influent and effluent concentrations of micropollutants from two slightly larger plants (serving 12-30 person equivalent) are also included. These micropollutants consisted of 19 selected pharmaceuticals, caffeine and the sweetener Acesulfame K, and 15 phthalates. The purpose of the collected dataset was to investigate the treatment efficiency of package plants operating in cold climate conditions throughout different seasons. The samples were collected in the northern regions of Sweden (Norrbotten) and ... : Uppgifterna inkluderar inkommande och utgående avloppsvattenkoncentrationer av traditionella parametrar uppmätt i minireningsverk som betjänar enstaka hus eller små samhällen (2-30 personekvivalenter). Parametrarna som analyseras inkluderar organiskt material, suspenderade ämnen, näringsämnen (fosfor- och kväveföreningar) och indikatorbakterier, samt andra fysikalisk-kemiska parametrar som temperatur, pH och turbiditet samt klorid för att upptäcka utspädningseffekter. Ytterligare inflödes- och avloppskoncentrationer av mikroföroreningar från två lite större anläggningar (betjänar 12-30 personekvivalenter) ingår också. Dessa mikroföroreningar bestod av 19 utvalda läkemedel, koffein och sötningsmedlet Acesulfame K, och 15 ftalater. Syftet med den insamlade datamängden var att undersöka reningseffektiviteten hos minireningsverk som arbetar under kalla klimatförhållanden under olika årstider. Proverna samlades in i de norra delarna av Sverige (Norrbotten) och Finland (Norra Österbotten och Lappland) som ...